VISUALISASI DAN KARAKTERISASI TANAH LONGSORAN STUDI KASUS: KECAMATAN SINJAI TENGAH PROVINSI SULAWESI SELATAN - Linda Handayani; Fourier D. E. Latief; Rustan Rustan; Acep Purqon (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Central Sinjai is one of the sub districts in Sinjai, South Sulawesi Province. Central Sinjai is an area that prone of landslide. This is caused by the dominance of the hills and mountains form and it has a steep slope. Landslide in Sinjai is one of the disasters that are difficult to avoid, because it is one of the consequences of geographic location. Nevertheless, it can be prevented and minimized risks by conducting fundamental research. The aims of this research are to visualize soil landslides samples in 3D. This samples were taken in prone area of landslides with different coordinates. In addition, in this research also analize physis paramater of the samples. This reserach is very important to look up the real condition of the soil landslides. This Research will be a fundamental research to understand the characteristic of landslides in Sinjai, then could be a refference to anticipate and reduce a risk of landslides. Image in 2D were taken by Micro-CT Scanner, Sky Scan 1173. Scanning Process use X-Ray with voltage 130 kV, current 60 Î¼A, and camera resolution 1120x1120 pixel. Then, reconstruction image will be visualized by Data Viewer and CT Vox. CT An is using to characterising physics parameter. The results of this research has showed that landslide soil structure is composed by small grain and the soil have low density. The porosity of soil lanslide is 26,73%. Keywords: Visualisation, Characterisation, Soil Landslides, South Sulawesi